Trust, psychological safety and viability in work groups: team psychological safety as a mediator between team trust and team viability - Quintana, Camila Flores (2019)
Dissertação de Mestrado em Psicologia do Trabalho, das Organizações e dos Recursos Humanos apresentada à Faculdade de Psicologia e de Ciências da Educação